The drummer boy : marching to the Civil War - Turner, Ann Warren; Hess, Mark (New York : HarperCollins, 1998)
A thirteen-year-old soldier, coming of age during the American Civil War, beats his drum to raise tunes and spirits and muffle the sounds of the dying.
School Library Journal.
Kirkus Review.
5.5
K-3
Keywords: United States -- History -- Civil War, 1861-1865 -- Juvenile fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction